Lippincott's Q & A review for NCLEX-RN - Billings, Diane McGovern (Lippincott Williams & Wilkins, 2008)
This top selling NCLEX-RN review package reflects the most current NCLEX-RN test plan and contains more than 5,500 total test questions, including the new alternate-format questions, to help students practice taking the licensing exam. Organized by practice area,-childbearing family/neonate, child health, adult medical-surgical, and psychiatric and mental health, the book contains more questions than any other NCLEX-RN review. The author clearly explains the rationale for correct and incorrect answers. Six comprehensive tests resembling the format of the NCLEX-RN are included. A back-of-book CD-ROM contains more than 1,000 questions. The book follows the NCLEX-RN test plan, covering the four major categories of client needs: Safe, Effective Care Environment, Health Promotion and Maintenance, Psychosocial Integrity, and Physiological Integrity. Additionally, like the test plan, the book integrates the following concepts and processes: nursing process, caring, communication/documentation, and teaching/learning. Although the questions in the book are written to test all levels of the cognitive domain (knowledge, comprehension, application, and analysis), the majority of questions in this book are written at the application and analysis levels of the cognitive domain, challenging students to improve their critical thinking skills and apply knowledge to clinical situations
Rev. ed. of: Lippincott's review for NCLEX-RN. 8th ed. c2005
Keywords: National Council Licensure Examination for Registered Nurses -- Study guides.; Nursing -- Examinations, questions, etc.; Nursing Care -- Examination Questions.